TREATMENT OF ULCERATIVE COLITIS IN FOLK MEDICINE WITH HYPERICUM, ACHILLEA MILLEFOLIUM, PLANTAGO, CALENDULA OFFICINALIS, INULA HELENIUM AND MATRICARIA - Ibragim R. Askarov,; Khabibullo N. Kodirov , (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article analyzes data on rejuvenation and an increase in the number of patients with Ulcerative colitis, one of the most common gastroenterological diseases in the world. The main attention is paid to the study of the factors contributing to the occurrence of this disease, the side effects of drugs used today to treat the disease on the human body. The biological activity of the food additive ” Hypericum, achillea millefolium, plantago, calendula officinalis, inula helenium and matricaria ", the chemical composition of medicinal plants used for its treatment, as well as on the methods of their use and mechanisms of action, recommended for the prevention and treatment of this disease, as well as the relevant conclusions were drawn.